2022
DOI: 10.1186/s12936-022-04364-7
|View full text |Cite
|
Sign up to set email alerts
|

The use of routine health facility data for micro-stratification of malaria risk in mainland Tanzania

Abstract: Background Current efforts to estimate the spatially diverse malaria burden in malaria-endemic countries largely involve the use of epidemiological modelling methods for describing temporal and spatial heterogeneity using sparse interpolated prevalence data from periodic cross-sectional surveys. However, more malaria-endemic countries are beginning to consider local routine data for this purpose. Nevertheless, routine information from health facilities (HFs) remains widely under-utilized despit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
27
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 53 publications
(46 reference statements)
5
27
1
Order By: Relevance
“…There was very high heterogeneity across the five villages which are located close to each other, suggesting that there are critical factors associated with the micro-geographic pattern of malaria in this community. The findings are similar to what was reported elsewhere [47], where high level of heterogeneity at micro-geographic levels was reported within the wards from 80 councils of Mainland Tanzania. Although few studies have assessed the prevalence of malaria in asymptomatic individuals of all age groups in Tanzania, the prevalence reported in this study is likely the highest in the country in recent years.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…There was very high heterogeneity across the five villages which are located close to each other, suggesting that there are critical factors associated with the micro-geographic pattern of malaria in this community. The findings are similar to what was reported elsewhere [47], where high level of heterogeneity at micro-geographic levels was reported within the wards from 80 councils of Mainland Tanzania. Although few studies have assessed the prevalence of malaria in asymptomatic individuals of all age groups in Tanzania, the prevalence reported in this study is likely the highest in the country in recent years.…”
Section: Discussionsupporting
confidence: 91%
“…This suggests that efforts to eliminate malaria need to target groups at high risk, and to consider and concurrently implement strategies for poverty reduction. Although previous studies showed high heterogeneity of malaria transmission and risk at macro-geographic levels [47,55], there is paucity of studies of micro-geographic variations of malaria burden and associated risk factors [47]. Thus, more studies are required to further assess malaria burden and risk factors associated with its transmission at different geographic levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study, the prevalence of malaria infections ranged from 15% to 25% by microscopy and 24% and 35% for RDTs, and these variations were not significantly associated with the key features studied, the location of the dispensary, and a big pond. These findings are in contrast to what was reported by NMCP in 2020 and others in 2022 that Muheza district council including the study villages had an overall high prevalence which was 30% and above [25,26,28]. Among the study villages, Mamboleo had a slightly higher prevalence of malaria infections than the other two villages, possibly due to the presence of the pond within the village.…”
Section: Discussioncontrasting
confidence: 84%
“…In the 2020 malaria stratification, the country was divided into five epidemiological strata with councils and regions of high, moderate, low, and very low, and the urban stratum with 116/184 (63.1%) of the councils in high/moderate while the low/very low strata had 68/184 (36.9%) of all the councils [16]. The next round of stratification was done in 2022 and showed a slight increase of councils (70/184 (38.0%) located in low and very low malaria transmission [26]. Based on stratification, NMCP designed and has been implementing area-specific interventions with the goal of burden reduction in areas with high and moderate transmission and eliminating malaria in low/very transmission areas [25].…”
Section: Introductionmentioning
confidence: 99%